2017
DOI: 10.1111/add.13881
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of purchase price of legal and illicit cigarettes in urban retail environments in 14 low‐ and middle‐income countries

Abstract: Background/AimsTo estimate and compare price differences between legal and illicit cigarettes in 14 low‐ and middle‐income countries (LMIC).DesignA cross‐sectional census of all packs available on the market was purchased.SettingCigarette packs were purchased in formal retail settings in three major cities in each of 14 LMIC: Bangladesh, Brazil, China, Egypt, India, Indonesia, Mexico, Pakistan, the Philippines, Russia, Thailand, Turkey, Ukraine and Vietnam.ParticipantsA total of 3240 packs were purchased (rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…One study found, for example, that the median price of illicit cigarettes was in fact higher than legal cigarettes in six LMICs (Bangladesh, India, Pakistan, Philippines, Thailand and Vietnam), but lower in three (Turkey, Ukraine and China). 2 The authors highlighted taste and brand preference by consumers as likely contributory factors in countries where the price of illicit cigarettes is higher, while also noting that the illicit market is not a homogeneous entity. 2 The study by Joossens et al 1 focused on smuggling of premium cigarettes thought to dominate the illicit market at the time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found, for example, that the median price of illicit cigarettes was in fact higher than legal cigarettes in six LMICs (Bangladesh, India, Pakistan, Philippines, Thailand and Vietnam), but lower in three (Turkey, Ukraine and China). 2 The authors highlighted taste and brand preference by consumers as likely contributory factors in countries where the price of illicit cigarettes is higher, while also noting that the illicit market is not a homogeneous entity. 2 The study by Joossens et al 1 focused on smuggling of premium cigarettes thought to dominate the illicit market at the time.…”
Section: Introductionmentioning
confidence: 99%
“…2 The authors highlighted taste and brand preference by consumers as likely contributory factors in countries where the price of illicit cigarettes is higher, while also noting that the illicit market is not a homogeneous entity. 2 The study by Joossens et al 1 focused on smuggling of premium cigarettes thought to dominate the illicit market at the time. Other sources of illicit trade have since emerged including illegal or undeclared manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco control researchers around the world often triangulate several methods to improve the precision of their estimates of the magnitude of illicit trade [ 24 ]. The volume of scientific literature is skewed towards the high- and upper middle-income countries [ 1 , 4 , 5 , 6 , 7 , 17 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] relative to the low- and lower middle-income countries [ 11 , 24 , 35 , 36 , 37 , 38 ]. This is perhaps due to the issue of data availability and research capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, evidence from other countries shows that illicit cigarettes are often more, rather than less, expensive than legal offerings. 12 In broad terms, however, the equivalent retail sales value of illicit cigarettes can be estimated by multiplying the number of illicit cigarette sticks by their average retail price in the legal, retail market. In India, the average retail price of 10 cigarette sticks was reported to be about ₹87 (US$ 1.34) in 2016 to 2017.…”
Section: Methodsmentioning
confidence: 99%